2012
DOI: 10.1111/lcrp.12000
|View full text |Cite
|
Sign up to set email alerts
|

The association between investigative interviewers' knowledge of question type and adherence to best‐practice interviewing

Abstract: It is well established that not all investigative interviewers adhere to 'best-practice' interview guidelines (i.e., the use of open-ended questions) when interviewing child witnesses about abuse. However, little research has examined the sub skills associated with open question usage. In this article, we examined the association between investigative interviewers' ability to identify various types of questions and adherence to open-ended questions in a standardized mock interview. Study 1, incorporating 27 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Recent studies have begun to highlight the benefits of having interviewer trainees code and objectively evaluate their own interviews (Cederborg, Alm, Lima da Silva Nises, & Lamb, ; Stolzenberg & Lyon, ). Guided self‐evaluation not only reduces the professional dependence of investigators on mentors and supervisors, but fosters the skilled identification of successful interventions (Powell, Benson, Sharman, & Guadagno, ; Yii, Powell, & Guadagno, ) as well as the ability to critically evaluate adherence to best practice guidelines (Cederborg, Alm, & Lima da Silva Nises, & Lamb, ; Myklebust & Bjørklund, ; Orbach et al, ; Price & Roberts, ) and is greatly appreciated by trainees (Powell & Wright, ). Such training often involves teaching interviewers to code their own interviews systematically using scientific procedures and formal coding schemes (Cederborg et al, ; Warren et al, ; Yi et al, ).…”
Section: Child Forensic Interviewer Training Studiesmentioning
confidence: 99%
“…Recent studies have begun to highlight the benefits of having interviewer trainees code and objectively evaluate their own interviews (Cederborg, Alm, Lima da Silva Nises, & Lamb, ; Stolzenberg & Lyon, ). Guided self‐evaluation not only reduces the professional dependence of investigators on mentors and supervisors, but fosters the skilled identification of successful interventions (Powell, Benson, Sharman, & Guadagno, ; Yii, Powell, & Guadagno, ) as well as the ability to critically evaluate adherence to best practice guidelines (Cederborg, Alm, & Lima da Silva Nises, & Lamb, ; Myklebust & Bjørklund, ; Orbach et al, ; Price & Roberts, ) and is greatly appreciated by trainees (Powell & Wright, ). Such training often involves teaching interviewers to code their own interviews systematically using scientific procedures and formal coding schemes (Cederborg et al, ; Warren et al, ; Yi et al, ).…”
Section: Child Forensic Interviewer Training Studiesmentioning
confidence: 99%
“…The computer-assisted self-assessment activities in this study were based on prior research that has shown them to be effective (Benson & Powell, 2015a;Brubacher et al, 2015;Powell, Cavezza, et al, 2010;Yii et al, 2014). Some key components of this prior body of work, however, could not be included.…”
Section: Computer-assisted Learningmentioning
confidence: 99%
“…When interviewers have a good grasp of the different types of open‐ended questions that best elicit narrative detail, they are more likely to demonstrate effective interviewing (Yii, Powell, & Guadagno, 2014). The questions that best facilitate narrative (story) detail fall into three categories.…”
Section: Research Underlying the Core Phases And Variants Of The Simmentioning
confidence: 99%